Overcoming communication barrier through corporate social responsibility of British American Tobacco Bangladesh - Tabassum, Redhowana (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.